2004
DOI: 10.4315/0362-028x-67.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Escherichia coli O157:H7 and Salmonella enterica Serovar Enteritidis in Chicken Manure by Larvae of the Black Soldier Fly

Abstract: Green fluorescent protein-labeled Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis were inoculated at 10(7) CFU/g into cow, hog, or chicken manure. Ten- or 11-day-old soldier fly larvae (Hermetia illucens L.) (7 to 10 g) were added to the manure and held at 23, 27, or 32 degrees C for 3 to 6 days. Soldier fly larvae accelerated inactivation of E. coli O157:H7 in chicken manure but had no effect in cow manure and enhanced survival in hog manure. The initial pH values of the hog and chicken m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
224
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(245 citation statements)
references
References 29 publications
4
224
2
3
Order By: Relevance
“…No identification of the specific coliform species was performed; however, it is likely that a large part of the coliforms included in the analyses were not E. coli. Erickson et al (2004) demonstrated a greater reduction in E. coli O157:H7 at 27-31°C in fly larvae-treated chicken manure compared to the reduction found in cattle manure. The reduction was increased with increasing temperature and similar reduction as observed in this study was observed in chicken manure at 23°C.…”
Section: Hygienic Quality Of Treatment Residuementioning
confidence: 99%
See 3 more Smart Citations
“…No identification of the specific coliform species was performed; however, it is likely that a large part of the coliforms included in the analyses were not E. coli. Erickson et al (2004) demonstrated a greater reduction in E. coli O157:H7 at 27-31°C in fly larvae-treated chicken manure compared to the reduction found in cattle manure. The reduction was increased with increasing temperature and similar reduction as observed in this study was observed in chicken manure at 23°C.…”
Section: Hygienic Quality Of Treatment Residuementioning
confidence: 99%
“…Chicken manure is considerably higher in ammonia than cattle manure (Paul and Beauchamp 1989); uncharged ammonia is well known to be toxic to microorganisms and as the concentration of uncharged ammonia increases with temperature (Nordin et al 2009). The reduction of E. coli observed by Erickson et al (2004) in chicken manure and the increased reduction observed at elevated temperatures could therefore have been caused by increased concentration of uncharged ammonia and be unrelated to larval activity. The mechanism behind the reduction of salmonella observed in this study is not known.…”
Section: Hygienic Quality Of Treatment Residuementioning
confidence: 99%
See 2 more Smart Citations
“…2). It utilizes this waste and can simultaneously kill pathogenic bacteria such as Escherichia coli or Salmonella enterica present in, for instance, chicken or cattle manure (Erickson et al 2004;Liu et al 2008). It has even been proposed as a sanitation method for getting rid of human feces (Lalander et al 2013;Banks et al 2014).…”
Section: Reducing Organic Wastementioning
confidence: 99%